The Interpretation of Hadits Prohibits Settling with Non-Muslims - Muhammad Imran; Arifuddin Ahmad; Abustani Ilya (Universitas Darussalam Gontor, 2019)
Islam is a religion with universal teachings covering all lines of human life from various aspects. That is, that Islam has taught its people how to become real human beings as caliphs on this earth. All activities of a Muslim are arranged in two important guidelines, namely the Qur’an and Hadits. It is undeniable, that sometimes the texts of the Qur’an and Hadits are found to be contrary to Islam as the religion carrying out the mission of seclusion. However, these texts must be comprehended in their entirety and comprehensively by using their knowledge so that they gain a comprehensive understanding of a problem and do not seem to be in a hurry to conclude. In the study of hadits, the use of the knowledge Ma’a>ni> al-Hadi>ts becomes very important in understanding the substance and meaning of a hadits, for example the hadits prohibited from living with non-Muslims, at a glance this tradition presents Islam as an exclusive religion. But with the use of knowledge Ma’a>ni> al-Hadi>ts in understanding this hadits, it will get an objective conclusion, so as not to give a negative impression on Muslims.",